Inventory control heuristic for a perishable item under stochastic demand and restricted batch size - Ani, Angelo C. (Philippine Engineering Journal)
This paper considers a type of inventory problem that deals with perishable item. The problem, which the authors believe has its main application in quick-service systems, such as fast food restaurants and similar systems, assumes that the item has a fixed lifetime and fixed lead time. The production of the item uses limited-capacity equipment that prepares the item in batches. Inventory review is done periodically. Demand for the item exhibits seasonal fluctuations throughout the planning horizon, and shortage results in lost sales. Unsold items exceeding allowed shelf life are set aside for disposal. Two heuristics were developed in order to identify the number of batches to be prepared at the start of each period. Cost considerations include setup costs, shortage cost, and excess cost. As part of the research, the heuristics were tested using real instances from an actual system. The approach is found to be successful in finding satisfactory solutions for the realistic target cases and specified metrics.